IMPLEMENTATION OF SHARIA BANKS’ SOCIAL FUNCTION AND THE IMPACT ON WELFARE OF PADANGSIDIMPUAN SOCIETY - Nofinawati Nofinawati (AL-QARDH, 2018)
Social function of Sharia Banks is to receive funds i.e. zakat, infaq, sedekah, wakaf, hibah, and distribute them in accordance to sharia laws under the banks’ name or amil zakat institutions appointed by the government. This function is an aspect that distinguishes sharia banks and conventional ones. In sharia law, social function and other functions cannot exist without the other. The implementation of social function in Kota Padangsidimpuan is in accordance with legal basis which is UU No. 21 tahun 2008. However, PT. Bank SUMUT Syariah KCS Padangsidimpuan has no authority to distribute social fund due to its existence as Islamic Windows. The implementation actually has positive impact on the welfare of the society despite being temporary. While it is only impactful towards those who receive the fund, the distribution is helpful.